Integrated model for the prenatal diagnosis and postnatal surgical treatment of total anomalous pulmonary venous connection: A multidisciplinary collaborative experience and preliminary results. Issue 11 (2nd September 2019) - Yang, Lijuan; He, Xiaomin; Lu, Yu; Huang, Fan; Shi, Guocheng; Chen, Huiwen; Zheng, Jinghao; Zhu, Zhongqun; Chen, Ping
Abstract: Background: This study aimed to evaluate an integrated model for the prenatal diagnosis and postnatal treatment of total anomalous pulmonary venous connection (TAPVC). Methods: From January 2014 to December 2018, 11 patients were considered as a prenatally diagnosed group, who would accept the integrated model for prenatal diagnosis and postnatal treatment of TAPVC. Besides, 25 patients as postnatally diagnosed group underwent emergency surgery during the corresponding period at the same age. The perioperative status, survival and risk factors for death were compared between the two groups. Results: In a prenatally diagnosed group, three pregnant women chose termination; eight patients followed the integrated model, and their newborns were rapidly transported to a children's hospital within 24 hours after birth. Other than one patient who was prenatally diagnosed with infracardiac type was later confirmed as a mixed type of TAPVC, the prenatal and postnatal diagnoses of the other seven patients were consistent. The 30‐day, 1‐year, and 5‐year survival rates in the prenatally diagnosed group were 100%, 100%, and 100%, while those in the postnatally diagnosed group were 92%, 87.8%, and 87.8%, without significant difference ( P > .05). Although Fisher's exact test indicated that an oxygen saturation <70% at admission might be an independent predictor of mortality ( P < .01), none of the risk factors for death were significantly different by multivariate Cox regression analysis. Conclusion: The integrated model of prenatal diagnosis and postnatal treatment by multidisciplinary collaboration could lead to satisfactory outcomes, and prenatal diagnosis combined with postnatal oxygen saturation evaluation would facilitate early intervention for TAPVC.